What Is the Role of AI in Antibody Drug Development? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Antibody-drug conjugates (ADCs) are a rapidly growing class of cancer therapeutics that combine the specificity of monoclonal antibodies with the potency of ...
Keywords: Drug Discovery and Pharmaceutical AI; Antibody; Development; Artificial Intelligence; Deep Learning